Cover Image, Volume 12, Issue 4. (11th June 2020) - Zezina, Ekaterina; Sercan‐Alp, Oezen; Herrmann, Matthias; Biesemann, Nadine
Abstract : The cover image is based on the Advanced Review Glucose transporter 1 in rheumatoid arthritis and autoimmunity by Ekaterina Zezina et al., https://doi.org/10.1002/wsbm.1483 . Abstract : The cover image is based on the Advanced Review Glucose transporter 1 in rheumatoid arthritis and autoimmunity by Ekaterina Zezina et al., https://doi.org/10.1002/wsbm.1483 .